Yurisdiksi ICC terhadap Negara non Anggota Statuta Roma 1998 - Sefriani Sefriani (Fakultas Hukum Universitas Islam Indonesia, 2007)
State Parties of Rome Satute 1998 have a territorial jurisdiction over the crimes which occured on their territorial. This is applied for all authors which come from the state parties and non state parties.